A virtual path routing algorithm for ATM networks based on the equivalent bandwidth concept - Bür, Kaan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1998., 1998)
The coexistence of services with different quality of service (QoS) requirements in today's networks makes the efficient use of resources a major issue. It is desirable to improve network efficiency by adaptively assigning resources to services that have different bandwidth demands. Implementing Broadband Integrated Services Digital Networks (B-ISDN) therefore requires a network control scheme that can absorb unexpected traffic fluctuations. ATM technology provides this flexibility by virtualizing network resources through the use of the VP concept. The traffic demand of new services in a B-ISDN environment may be highly bursty and difficult to predict. The implementation of the equivalent bandwidth concept provides an efficient method to estimate capacity requirements. In this study, a method for designing a VP-based ATM network is proposed. The developed heuristic algorithm uses the equivalent bandwidth concept to compute the capacity requirements of the connection requests. This way, the desired QoS defined by the cell loss probability is guaranteed. The algorithm applies VP routing and separation techniques to minimize the maximum link utilization under processing delay constraints. The quality of the solutions achieved by the heuristic design algorithm is compared to several competitors under varying network topologies and traffic conditions. The observations on the algorithm performance show that the developed method is able to facilitate an efficient use of network resources through the introduction of VPs.
Keywords: Computer networks.; Integrated services digital networks.; Broadband communication systems.; Asynchronous transfer mode.